Structure and Properties of PLA Nanocomposite Feedstock for Additive Manufacturing - Greeley, Duncan; Gritton, Jack; Minneci, Robert; Plymill, Austin; Bhat, Gajanan (European Journal of Applied Sciences, 2022)
Additive manufacturing is continuing to grow with a large potential for replacement of traditionally manufactured parts, part repair, and prototype development due to complexity of allowable part geometry and low raw material use. However mechanical properties of parts processed through additive manufacturing typically suffer in comparison. The goal of this study was to develop an improved and sustainable feedstock material for additive manufacturing through reinforcement of polylactic acid with nanoparticles such as graphene and multiwalled carbon nanotubes. Composites with loadings of 0.1, 0.2, and 0.5 wt% of each reinforcement were extruded to form filament feedstock, and tensile and impact specimens were printed using a Lulzbot Mini according to ASTM D638 and D256 test methods. Mechanical properties were evaluated through tensile and impact testing, while fracture surfaces were analyzed using a scanning electron microscope. Thermal properties of the feedstock material and post-printed material were analyzed with differential scanning calorimetry. Reinforcements led to a moderate increase in mechanical properties with the 0.2 wt% loading of graphene showing a 47% increase in tensile strength, a 17% increase in modulus, and 12% increase in energy absorbed upon fracture. The 0.1 wt% loading of MWCNT had respective increases of 41%, 16%, and 9%, in tensile strength, modulus and fracture energy. Adding small amount of nanoparticles during processing is easy to accomplish and the improvement in performance may be justified for many applications.